Separating speed and ability to displace roadblocks during DNA translocation by FtsK. - Crozat, E; Meglio, A; Allemand, J; Chivers, C; Howarth, M; Vénien-Bryan, C; Grainge, I; Sherratt, D (2010)
FtsK translocates dsDNA directionally at >5 kb/s, even under strong forces. In vivo, the action of FtsK at the bacterial division septum is required to complete the final stages of chromosome unlinking and segregation. Despite the availability of translocase structures, the mechanism by which ATP hydrolysis is coupled to DNA translocation is not understood. Here, we use covalently linked translocase subunits to gain insight into the DNA translocation mechanism. Covalent trimers of wild-type subunits dimerized efficiently to form hexamers with high translocation activity and an ability to activate XerCD-dif chromosome unlinking. Covalent trimers with a catalytic mutation in the central subunit formed hexamers with two mutated subunits that had robust ATPase activity. They showed wild-type translocation velocity in single-molecule experiments, activated translocation-dependent chromosome unlinking, but had an impaired ability to displace either a triplex oligonucleotide, or streptavidin linked to biotin-DNA, during translocation along DNA. This separation of translocation velocity and ability to displace roadblocks is more consistent with a sequential escort mechanism than stochastic, hand-off, or concerted mechanisms.